THE EFFECT OF TRUST TO GOVERNMENT, MORAL OBLIGATION AND COMPLIANCE COSTS ON TAXPAYERS COMPLIANCE BEHAVIOR - Muslichah, Muslichah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
The aim of this study is to examine the direct and indirect effect of trust to government, costs of compliance and moral obligation on taxpayer compliance behavior. This study was conducted in East Java. The respondents of the study are business taxpayers. Fourty three taxpayers participated in this study. The findings of this study show that: (1) the direct effect trust to government on taxpayer compliance behavior is positive and significant (2) the indirect effect of trust to government on taxpayer compliance behavior through moral obligation is positive and significant (3) the indirect effect of trust to government on taxpayer compliance behavior through costs of compliance is insignificant. This study contribute not only to the research literature but also to help government to develop strategies toward improving compliance. Keywords: trust to government, moral obligation, compliance costs, compliance behavior.